The IRONy of Iron-overload and Iron-deficiency in Chronic Obstructive Pulmonary Disease. - Cloonan,SM; Mumby,S; Adcock,IM; Choi,AMK; Chung,KF; Quinlan,GJ (American Journal of Respiratory and Critical Care Medicine, 2017)
Chronic obstructive pulmonary disease (COPD) is a debilitating inflammatory lung disease associated with cigarette smoking and is third leading cause of death worldwide. With the recent emergence of genome wide association studies (GWAS), the identification of multiple COPD susceptibility genes has enhanced and expanded our understanding of the pathogenic mechanisms associated with this debilitating lung disease. An example of such a pathogenic mechanism is the role of iron metabolism in the onset and progression of COPD. Historic observations of iron dysregulation in COPD can now be enlightened by the recent revelations that genetic polymorphisms in the gene iron regulatory protein-2 (IRP-2) associate with COPD susceptibility. A functional role for IRP-2 is supported by IRP-2 overexpression in murine models, that demonstrates cellular and mitochondrial iron accumulation in the lung linked with manifestations of experimental COPD. Increased IRP2 may explain the excessive iron deposition in alveolar macrophages and tissue in smokers and in patients with COPD. Changes in IRP2 expression may also associate with systemic iron mismanagement, which may explain the prevalence of systemic iron deficiency and iron-deficiency anemia in patients with COPD. It may also help to explain why patients with COPD and/or iron deficiency manifest altered responses to hypoxia including erythropoiesis and pulmonary hypertension. We provide a concise review of the role of iron in the pathogenesis, susceptibility and progression of COPD and highlight the prospective therapeutic interventions for treating both local and systemic iron dysregulation.